Person-Centered Expressive Arts: An Alternative Path to Counseling and Education. An interview with Natalie Rogers - Laura Guadiana Martínez (Universidad Autónoma de Baja California, 2003)
In this interview, Natalie Rogers PhD, expounds on how art and expression serve personal and group growth in Person Centered Expressive Arts Therapy. Adding to the legacy of her father Carl Rogers, creator of the Person Centered Approach, she describes the interweaving of her experiences as a therapist and woman, and how she afforded extra room in the process for intuition, creativity, emotions and the fascinating exploration of the human experience. Using modeling, sculpting, dance, painting, music, etc. she created a model which furthers the person's genuine expression and self knowledge. She sketches a profile of a facilitator who takes special care in creating an ambience where s/he not only does not judge the work, person, experience or results, but is on the contrary, empathetic and acceptant of the person and her experiences. Lastly, she discusses the applications of this approach to traditional educational settings, as well as some of the key training issues.